Evaluation of Fatty Acid Waste in the Synthesis of Oligo(Ether-Ester)s - S. Kocaman; A. Cerit; U. Soydal; M. E. Marti; G. Ahmetli (International Journal of Polymer Science)
In this study, the waste of sunflower oil refinement was converted to a fatty acid glycidyl ester (FAGE). An unsaturated oligo(ether-ester) (OEE) was synthesized by ring-opening polymerization using propylene oxide (PO) and FAGE. Oligo(ether-ester) production was achieved with a high yield of 80% at 5 h and 0°C when the mole ratio of PO : FAGE was 1 : 1. Synthesized OEE was characterized by FTIR and several chemical analysis methods. According to the TGA results, T5, T10, and T50 values of OEE-styrene copolymers increased up to a 7 : 3 mole ratio then decreased. The weight losses of these copolymers changed in the range of 3-5%. The data of longitudinal and transversal wave velocities showed that copolymers with styrene had better elastic properties and impact resistances compared to those with pure polystyrene.